Changing sediment and surface water processes increase CH4 emissions from human-impacted estuaries. (1st July 2020) - Wells, Naomi S.; Chen, Jian-Jhih; Maher, Damien T.; Huang, Peisheng; Erler, Dirk V.; Hipsey, Matthew; Eyre, Bradley D.
Abstract: Coastal waters are known to emit globally significant quantities of CH4, a potent greenhouse gas, but the potential of the rapid and ongoing human alterations to coastal areas to alter these emissions remains undefined. Here we addressed this gap by quantifying water-to-air CH4 fluxes and δ 13 C-CH4 values in sub-tropical estuaries at Low ( n = 3), Moderate ( n = 2), and High ( n = 3) levels of human modification (agricultural land use, wastewater discharge), and sediment-to-water CH4 fluxes from the major benthic habitats in representative Low, Moderate, and High systems. An increase in water-to-air CH4 fluxes from 9.7 µmol m −2 d −1 (Low) to 28 µmol m −2 d −1 (Moderate) to 47 µmol m −2 d −1 (High) was accompanied by a shift from hydrogenotrophic to acetoclastic production pathways. Unexpectedly, benthic CH4 production, which ranged from −48 µmol m −2 d −1 to +180 µmol m −2 d −1 between habitats, estuaries, and seasons, was not the primary driver of this shift. Sediments produced more CH4 (∼600%) than emitted from the Low estuary, ∼90% of CH4 emitted from the Moderate estuary, but only 9% of CH4 emitted from the High estuary. Instead, a combination of wastewater, groundwater, and apparent water column production caused a ∼ 3-fold increase in estuary CH4 emissions. Our findings indicate that human alterations to the source, rate, and pathways of CH4 production are driving a net increase in emissions from estuaries, demonstrating a need to redefine how we quantify 'anthropogenic' CH4 emissions.